Femmes. - Rassemblement des Femmes pour la Paix et le Bien-Etre (Bruxelles : Rassemblement des Femmes pour la Paix et le Bien-Etre, 1950)
Fonds Emilienne Brunfaut
Frans
Periodiek
Keywords: vredesbewegingen